2016
DOI: 10.1167/iovs.16-19197
|View full text |Cite
|
Sign up to set email alerts
|

Defective Autophagy in Diabetic Retinopathy

Abstract: High glucose upregulates autophagy but accumulates p62/SQTSM1 cargo due to lysosomal dysfunction, leading to massive VEGF release and cell death of rMCs. Lysosomal impairment and autophagic dysfunction are early events present in the pathogenesis of diabetic retinopathy (DR). This might be valuable for developing a novel therapeutic strategy to treat DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 35 publications
5
85
0
Order By: Relevance
“…Although anti-VEGF therapeutic strategies have been employed thus far, the involvement of additional cellular factors 30 and symptoms beyond angiogenesis 2,27,29 show that neovascular retinal diseases are multifactorial conditions for which currently available treatments may be inadequate to address. Additionally, these treatments require frequent administration on a long-term basis, 3 from which other issues may arise, including safety concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although anti-VEGF therapeutic strategies have been employed thus far, the involvement of additional cellular factors 30 and symptoms beyond angiogenesis 2,27,29 show that neovascular retinal diseases are multifactorial conditions for which currently available treatments may be inadequate to address. Additionally, these treatments require frequent administration on a long-term basis, 3 from which other issues may arise, including safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Although the links between cell death and pathological retinal angiogenesis have yet to be fully elucidated, including the exact mechanism(s) involved, increased apoptosis has been implicated in the release of VEGF in proliferative DR (PDR). 29 TUNEL-positive cells were observed in the inner and outer nuclear layers of the untreated (16.6 ± 4.2), mocktreated (17.4 ± 5.6), and control shRNA-treated (17.6 ± 3.6) groups of the rat OIR model (Fig. 4A).…”
Section: Antiapoptotic Ability Of Raav2-shmtor-gfpmentioning
confidence: 98%
“…In addition, autophagy inhibition reduced the activation of Müller cells and inhibited astrogliosis in damaged retinas, suggesting that the inhibition of autophagy prevents Müller cell activity during ischemia/reperfusion injury [58]. Lopes de Faria et al [59] reported that high glucose upregulated autophagy in retinal Müller cells and induced lysosomal impairment, which represent early events in the pathogenesis of diabetic retinopathy.…”
Section: Autophagy In Müller Cellsmentioning
confidence: 99%
“…However, this catabolic process cannot reach the final stage (degradation of the cargo) because of an increase in the lysosomal pH and a decrease in lysosomal enzyme activity. Treatments with autophagy inductors, such as rapamycin, have restored the normal flux and prevented the activation of apoptosis (Lopes de Faria et al., ).…”
Section: Antioxidant Pathwaysmentioning
confidence: 99%